(untitled) (City: History, Culture, Society, 2026)
The article traces the emergence and development of DCCC (Dnipro Center for Contemporary Culture) as a civic-driven institution that combines the presentation of contemporary artistic practices with sustained engagement with local contexts and urban communities. It outlines how an initiative shaped in the aftermath of the Revolution of Dignity—centered on the audiovisual and new media festival Konstruktsiia (since 2015)—evolved from a primarily “virtual” presence into multiple attempts to secure a permanent venue, culminating in a prototype: the temporary public space Stage:Stage (2017). The project’s international recognition (Special Mention at the European Prize for Urban Public Space 2018 and nomination for the EU Prize for Contemporary Architecture—Mies van der Rohe Award) is discussed as a turning point that helped enable negotiations for a long-term home. The text describes the launch of DCCC in the former provincial zemstvo building on Krutohirnyi Uzviz, the ongoing restoration process, and the residency-based institutional model bringing together NGO Kultura Medialna, Artsvit Gallery, and Alliance Française. Particular attention is paid to institutional transformations during Russia’s full-scale invasion: from suspension of activities to the establishment of a social hub (2022), and later the gradual return to programming (2023–2024) through the initiative “DCCC: We Work,” expanded international partnerships, and new infrastructures such as a 51-seat cinema, an Experimental Studio, and a concept shop as a critical design project. The article also maps DCCC’s core program lines—exhibitions, education, residencies, and film programs—as tools for supporting cultural life under wartime conditions